Regesten zur Geschichte der Juden in Österreich im Mittelalter, Band 1 Band 1: Von den Anfängen bis 1338 - Brugger, Eveline (Studien Verlag, 2005)
The still existing source material on the history of the Jews in Austria in the Middle Ages is unique in Europe. The huge number of sources give information on the economic, legal, and personal situation of the Jews as well as on the relationship between Christians and Jews. Yet so far, the medieval sources of the history of the Jews throughout today's Austria had not been collected. In the course of the project "Summary and Comments on Documents concerning the History of the Jews in Austria in the Middle Ages" the first volume of this source material which reaches from the beginnings until 1338 has now been finished. According to the selection criteria which include a reference to Jews and Austria, documents as well as historiography and literary sources have been collected and processed according to scientific criteria; the material contains a number of texts which have not been published at all or treated with regard to the Jewish aspect yet. The publication consists of a chronological series of document summaries; additionally, by means of comments which are added to the relevant document as well as an extensive index, the source text has been made accessible to the reader. The vast majority of the collection consists of diplomas concerning economic topics, followed by privileges, legal charters, and mandates. Among the economic sources, promissory notes and documents concerning pledges or sales are the most frequent types which clearly illustrates how Jews were forced into the money business. Due to its unique topic, this collection includes not only diplomas, but other types of sources as well, such as historiographic and literary texts. Although belonging to another category of sources, they provide information which is essential for a complete overview over the history of Jews in medieval Austria. This volume is the basis for a publication series which for the first time makes the unique source material on the history of the Jews in Austria in the Middle Ages accessible in a compiled way .